2019
DOI: 10.1177/0363546519851506
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Return to Sport and Weight Training After Repair of the Pectoralis Major Tendon

Abstract: Background: The use of routine patient-reported outcomes after repair of the pectoralis major tendon (PMT) is often prone to the ceiling effect owing to the high functional demand of those who sustain this injury. Hypothesis: A significant number of patients are expected to fail to achieve return to preoperative activity after PMT repair despite achieving significant improvements in functional score. Study Design: Case series; Level of evidence, 4. Methods: A prospectively maintained institutional database was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Yu et al 31 reported that 74% of patients returned to preinjury levels of sport. Liu et al 16 identified a lower rate with 50% returning to preinjury sport intensity and significant decreases in pectoralis strength. In the current study, both acute and chronic repairs still resulted in some postoperative residual pain, functional deficit, and loss of strength, as measured by bench press and push-ups.…”
Section: Discussionmentioning
confidence: 98%
“…Yu et al 31 reported that 74% of patients returned to preinjury levels of sport. Liu et al 16 identified a lower rate with 50% returning to preinjury sport intensity and significant decreases in pectoralis strength. In the current study, both acute and chronic repairs still resulted in some postoperative residual pain, functional deficit, and loss of strength, as measured by bench press and push-ups.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have examined functional outcome, with respect to percent of pre-injury bench-press, in the general population. 2,14,26,[45][46][47] Others have also reported excellent outcomes after PM injuries undergoing operative treatment in active-duty United States military personnel and military academy students. [48][49][50][51] Recently, Liu et al 26 demonstrated significantly reduced PM strength after PM injury at a mean 2-year follow-up, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…2,14,26,[45][46][47] Others have also reported excellent outcomes after PM injuries undergoing operative treatment in active-duty United States military personnel and military academy students. [48][49][50][51] Recently, Liu et al 26 demonstrated significantly reduced PM strength after PM injury at a mean 2-year follow-up, which is consistent with previous studies. 2,45,52 A prior study demonstrated that up to 40% of surgically treated recreational athletes had a greater than 20% deficiency of isokinetic strength when compared to the uninjured contralateral side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations